Global citizenship education in praxis : pathways for schools - Schultz, Anders, 1977-; Blom, Mads, 1974- (Multilingual Matters, 2023)
"This book examines the experience of combining internationalisation, intercultural competence and global citizenship in an upper secondary school in Denmark with links to schools in 15 countries. The book includes a description of the project by the teachers who have taken part and an analysis by researchers who have worked with them"-- Provided by publisher.
Keywords: Education and globalization -- Denmark.; World citizenship.; Education, Secondary -- Social aspects -- Denmark.; Multicultural education -- Denmark.; Éducation et mondialisation -- Danemark.; Citoyenneté mondiale.; Enseignement secondaire -- Aspect social -- Danemark.; Éducation interculturelle -- Danemark.; SOCIAL SCIENCE / Anthropology / Cultural & Social.; Education and globalization; Education, Secondary -- Social aspects; Multicultural education; World citizenship; Denmark